Simulating NEMA characteristics of the modular total-body J-PET scanner—an economic total-body PET from plastic scintillators. (1st September 2021) - Moskal, P; Kowalski, P; Shopa, R Y; Raczyński, L; Baran, J; Chug, N; Curceanu, C; Czerwiński, E; Dadgar, M; Dulski, K; Gajos, A; Hiesmayr, B C; et al.
Abstract: The purpose of the presented research is estimation of the performance characteristics of the economic total-body Jagiellonian-PET system (TB-J-PET) constructed from plastic scintillators. The characteristics are estimated according to the NEMA NU-2-2018 standards utilizing the GATE package. The simulated detector consists of 24 modules, each built out of 32 plastic scintillator strips (each with cross section of 6 mm times 30 mm and length of 140 or 200 cm) arranged in two layers in regular 24-sided polygon circumscribing a circle with the diameter of 78.6 cm. For the TB-J-PET with an axial field-of-view (AFOV) of 200 cm, a spatial resolutions (SRs) of 3.7 mm (transversal) and 4.9 mm (axial) are achieved. The noise equivalent count rate (NECR) peak of 630 kcps is expected at 30 kBq cc −1 . Activity concentration and the sensitivity at the center amounts to 38 cps kBq −1 . The scatter fraction (SF) is estimated to 36.2 %. The values of SF and SR are comparable to those obtained for the state-of-the-art clinical PET scanners and the first total-body tomographs: uExplorer and PennPET. With respect to the standard PET systems with AFOV in the range from 16 to 26 cm, the TB-J-PET is characterized by an increase in NECR approximately by factor of 4 and by the increase of the whole-body sensitivity by factor of 12.6 to 38. The time-of-flight resolution for the TB-J-PET is expected to be at the level of CRT = 240 ps full width at half maximum. For the TB-J-PET with an AFOV of 140 cm, an image quality of the reconstructed images of a NEMA IEC phantom was presented with a contrast recovery coefficient and a background variability parameters. The increase of the whole-body sensitivity and NECR estimated for the TB-J-PET with respect to current commercial PET systems makes the TB-J-PET a promising cost-effective solution for the broad clinical applications of total-body PET scanners. TB-J-PET may constitute an economic alternative for the crystal TB-PET scanners, since plastic scintillators are much cheaper than BGO or LYSO crystals and axial arrangement of the strips significantly reduces the costs of readout electronics and SiPMs.